Disentangling the relationship between sex-biased gene expression and X-linkage - Meisel, Richard P.; Malone, John H.; Clark, Andrew G. (Genome Research, 2012)
X chromosomes are preferentially transmitted through females, which may favor the accumulation of X-linked alleles/genes with female-beneficial effects. Numerous studies have shown that genes with sex-biased expression are under- or over-represented on the X chromosomes of a wide variety of organisms. The patterns, however, vary between different animal species, and the causes of these differences are unresolved. Additionally, genes with sex-biased expression tend to be narrowly expressed in a limited number of tissues, and narrowly expressed genes are also non-randomly X-linked in a taxon-specific manner. It is therefore unclear whether the unique gene content of the X chromosome is the result of selection on genes with sex-biased expression, narrowly expressed genes, or some combination of the two. To address this problem, we measured sex-biased expression in multiple Drosophila species and at different developmental time points. These data were combined with available expression measurements from Drosophila melanogaster and mouse to reconcile the inconsistencies in X-chromosome content among taxa. Our results suggest that most of the differences between Drosophila and mammals are confounded by disparate data collection/analysis approaches as well as the correlation between sex bias and expression breadth. Both the Drosophila and mouse X chromosomes harbor an excess of genes with female-biased expression after controlling for the confounding factors, suggesting that the asymmetrical transmission of the X chromosome favors the accumulation of female-beneficial mutations in X-linked genes. However, some taxon-specific patterns remain, and we provide evidence that these are in part a consequence of constraints imposed by the dosage compensation mechanism in Drosophila.